Navigating the Digital Shift: Insights into Technology, Education, and Employability in India: Examining the impact of technology integration on education and employability in India (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This research paper delves into the dynamic intersection of technology, education, andemployability in India. Through an intricate analysis of primary and secondary data, we evaluate themultifaceted impacts of technology integration, exploring its repercussions on learning outcomes and thedevelopment of employability skills.